Impact of ionophore monensin on performance and Cu uptake in earthworm Eisenia andrei exposed to copper-contaminated soil. (October 2016) - Zidar, Primož; Kos, Monika; Vogel-Mikuš, Katarina; van Elteren, Johannes Teun; Debeljak, Marta; Žižek, Suzana
Abstract: Exposure of beneficial soil organisms to chemical mixtures is of great concern and can result in unexpected deleterious consequences. We investigated the effects of concurrent soil contamination with monensin, a veterinary pharmaceutical and feed additive, and copper, on earthworm copper uptake and reproductive success. The animals were exposed for 14 or 28 days to both substances and the results showed that the Cu body burden of earthworms increases in the presence of monensin. The harmful effects of Cu on earthworm cocoon production were considerably higher when monensin was also present in the soil. To localise the copper in earthworm tissues, histological staining was performed using two different dyes (rubeanic acid and 5-4-( p -dimethylaminobenzylidene)-rhodanine). Laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) was used to quantify the Cu levels in the tissues. Cu was found predominantly in the gut wall. The Cu content in the body wall was at least ten times lower compared to the gut, but was proportional to the level of soil contamination. Concurrent soil contamination with monensin and copper resulted in higher earthworm Cu levels and in decreased reproductive success of these important soil decomposers. Highlights: Monensin could increase Cu bioaccumulation in earthworms. Monensin magnifies the harmful effect of copper on Eisenia andrei reproduction. LA-ICP-MS was successfully used to localise and quantify Cu in animal tissues.